The maritime transport of sculptures in the ancient Mediterranean - Velentza, Katerina, (Archaeopress Archaeology, 2022)
With a focus on the underwater context of sculptures retrieved from beneath the sea, this volume examines where, when, why and how sculptures were transported on the Mediterranean Sea during Classical Antiquity through the lenses of both maritime and classical archaeology.